2011
DOI: 10.1080/13647830.2010.535566
|View full text |Cite
|
Sign up to set email alerts
|

Applying nonlinear dynamic theory to one-dimensional pulsating detonations

Abstract: The dynamical behaviour of one-dimensional pulsating detonations was investigated in detail, with the aid of nonlinear theory tools such as phase plots and correlation dimension. The period-doubling cascade, as routes to deterministic chaos, is depicted through the transformations of the attractors' shapes. Using a correlation dimension method, the dimension of the attractors is determined and we show that the chaos within an one-dimensional pulsating detonation is deterministic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Limit cycle: the shock front dynamics In order to study the shock dynamics, it is useful to plot the phase plane d(p s /p N )/dt s versus p s /p N , as in Ng et al (2005) and Abderrahmane et al (2011). The numerical results shown in figure 7 reveal that, for large tube diameters and with E a = 22 RT 0 , the mean post-shock pressure stabilizes to a constant value after an initial transient.…”
Section: Detonation-velocity Deficitmentioning
confidence: 93%
See 2 more Smart Citations
“…Limit cycle: the shock front dynamics In order to study the shock dynamics, it is useful to plot the phase plane d(p s /p N )/dt s versus p s /p N , as in Ng et al (2005) and Abderrahmane et al (2011). The numerical results shown in figure 7 reveal that, for large tube diameters and with E a = 22 RT 0 , the mean post-shock pressure stabilizes to a constant value after an initial transient.…”
Section: Detonation-velocity Deficitmentioning
confidence: 93%
“…Following previous studies (see for example Zhang & Lee 1994, Ng et al 2005and Abderrahmane et al 2011, the dimensionless parameters are taken as γ = 1.2 and q/RT 0 = 50 so that comparisons can be made with the previously published results. Three test cases are considered with different E a .…”
Section: Problem Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, several authors have studied the dynamics of ideal one-dimensional detonations using a single-step Arrhenius model [3][4][5][6] by numerical means. These studies indicated that the activation energy (E a ) is the main parameter which controls the onset of the longitudinal instability for constant heat of reaction and specific heat ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been applied to the temporal behavior of the unstable combustion state observed not only in experiments (e.g., a thermal pulse combustor, 10 a ducted premixed combustor, [11][12][13] a spark ignition engine, 14,15 and swirling premixed flames 16 ) but also in the numerical solutions of sets of nonlinear differential equations derived from first principles (e.g., a thermal pulse combustor, 17 detonation, 18,19 and a spark ignition engine 20 ). In previous studies 6,[11][12][13] relevant to thermoacoustic combustion oscillations, the Grassberger-Procaccia (GP) algorithm, 21 used to obtain the correlation dimension as a class of the fractal dimension from an observational time series, was used to characterize the nonlinear nature.…”
Section: Introductionmentioning
confidence: 99%